Preparation, Characterization, and Evaluation of Electrospun Copolymer Nanofiber Membranes for Kerosene Removal from Aqueous Solution - Al-Musawy, Wafaa; Waisi, Basma; Al-Furaiji, Mustafa; Shehan, Ahmed; Jahangiri, Mehdi (Al-Khwarizmi Engineering Journal, 2026)
The petroleum sector generates significant amounts of oily wastewater requiring proper treatment before being released into the environment. The high stability, hydrophilicity, and large surface areas of membranes provide great opportunities for treating oily wastewater. For this work, electrospun nanofiber (ESNF) membranes of polyacrylonitrile (PAN) and polysulfone (PSU) were manufactured and evaluated for their separation capabilities. Multiple concentrations of the PAN and PSU polymers were used to optimize the copolymer nanofiber (NF) membranes. The water flux, oil rejection, and porosity evaluation of the membranes were compared. In addition, the surface and profile of the ESNF membranes were evaluated in terms of morphology and roughness, wettability, and tensile strength, and the results of scanning electron microscopy, atomic force microscopy, contact angle, and tensile tests were incorporated. The ESNF membranes provided positive results in the separation of oily wastewater. In particular, the best results were observed for the membranes composed of 75% PAN and 25% PSU, which reached 99.7% oil rejection, a maximum water flux of 400 L/m2.h, and 96% porosity, demonstrating great potential for wastewater treatment on an industrial scale. However, this study focused primarily on short-term performance evaluation. The long-term mechanical and chemical stability of ESNF membranes under continuous operational conditions remains to be examined.